Redundant mechanisms regulating the proliferation vs. differentiation balance in the C. elegans germline - Vanden Broek, Kara; Han, Xue; Hansen, Dave (Frontiers in Cell and Developmental Biology, 2022)
The proper production of gametes over an extended portion of the life of an organism is essential for a high level of fitness. The balance between germline stem cell (GSC) proliferation (self-renewal) and differentiation (production of gametes) must be tightly regulated to ensure proper gamete production and overall fitness. Therefore, organisms have evolved robust regulatory systems to control this balance. Here we discuss the redundancy in the regulatory system that controls the proliferation vs. differentiation balance in the C. elegans hermaphrodite germline, and how this redundancy may contribute to robustness. We focus on the various types of redundancy utilized to regulate this balance, as well as the approaches that have enabled these redundant mechanisms to be uncovered.